Desorganização como preditor de resistência ao tratamento e desfechos desfavoráveis na esquizofrenia - Ortiz, Bruno Bertolucci [UNIFESP] (2019)
The heterogeneous outcomes and symptoms in schizophrenia hinder the development of more effective diagnostic methods and treatments. Patients with greater severity of disorganized symptoms appear to be a distinct group, with poor response to conventional antipsychotics and poor outcome. Disorganized syndrome then applies to be a valid marker to identify a more homogeneous subgroup of disease. General objective: To validate disorganization as a predictor of unfavorable outcomes. The following outcomes were investigated in 5 studies: treatment resistance, global severity, functional impairment and symptom progression. Methods: Three samples were included in the analyzes: 1- Longitudinal sample (n = 203), with patients evaluated at admission and discharged during hospitalization in the psychiatry ward of Hospital Luzia de Pinho Melo - included in the five studies. 2- Cross-sectional sample (n = 207) of patients with multiple episodes from the schizophrenia outpatient clinic (Schizophrenia Program- Proesq, UNIFESP) - included in three studies. 3- A cohort (N = 55) of first-episode from Santa Casa de Misericórdia of São Paulo - included in one study. In all samples, the diagnosis of schizophrenia was confirmed by the SCID-I and symptom intensity was assessed using the Positive and Negative Symptoms Syndrome Scale (PANSS), Calgary Depression Scale for Schizophrenia (Calgary), Clinical Global Impression (CGI) and the Global Assessment of Functioning Scale (GAF). Results: Study 1: Eighty-five patients classified 13 according to traditional subtypes were compared for symptom severity and prevalence of treatment resistant schizophrenia (TRS). Patients with disorganized schizophrenia had a higher prevalence of ERT (60%) than paranoid schizophrenia (20%) (Chi-square = X value, p = 0.001). Study 2: The positive, disorganized and negative PANSS dimensions were compared for overall severity with CGI in the acute and stable phase in patients from 3 different centers (n = 298). The disorganized dimension presented the highest correlation with the CGI (0.86). Study 3: In patients from 2 different centers (n = 247), the dimensions of PANSS were compared with functioning in the acute, stable and remission phase. Increased disorganization at baseline predicted non-remission after treatment (p = 0.007; OR = 1.18). It was the dimension that most impaired functioning of patients in the acute phase (p <0.001). Study 4: Patients from 2 different centers (n = 203) were separated into 3 groups (first episode, with up to 5 years of disease and with more than 5 years of disease) and the intensity of each dimension were compared. The disorganized dimension presented the largest progressive increase in intensity among the first episode groups, up to 5 years of disease and more than 5 years of disease. Study 5: In a discovery sample (n = 164), a predictive model of TRS was built based on PANSS items, which were tested in a replication sample (n = 207). The accuracy of the model was tested on a ROC curve in the exploration and replication samples. The sensitivity and specificity of the exploration sample and the replication sample were, respectively, 77.8% and 83.3%, 72.3% and 74.4%. Conclusion: Integrating dimensional and categorical aspects into the psychopathology of schizophrenia has the potential to generate empirical validated data for both clinical practice and research. Dimensions and categories are still the most accessible diagnostic tools for the clinician. New syndrome models associated with clinical outcomes will be instrumental in progressively progressing to precision medicine in psychiatry.